2018
DOI: 10.1051/ijmqe/2018006
|View full text |Cite
|
Sign up to set email alerts
|

Results of the round robin calibration of reference solar cells within the PhotoClass project

Abstract: An intercomparison of terrestrial photovoltaic (PV) calibrations was performed among a number of European calibration and testing laboratories that participated in the European Metrology Research Program (EMRP) project “PhotoClass”. The purpose of this intercomparison was to evaluate the comparability of calibration and testing services within the stated uncertainties of the individual laboratories. The calibration objects were two world photovoltaic scale (WPVS)-type reference solar cells, one made from cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…A round-robin among nine different laboratories conducted within the European Metrology Research Programme concluded that the standard deviation of the different calibration values for the same reference cell was 0.81%. 19 An intercomparison of high-efficiency c-Si module calibration between five reference Asian and European laboratories showed a short-circuit current agreement of the same order. 20 Calibration certificates of PV modules measured at STC from accredited laboratories typically declare that uncertainty in short-circuit current, which is closely the same as uncertainty in G when the modules are used as irradiance sensors, is about u CAL G = 1.8%.…”
Section: Uncertainty Derived From G and T C Sensorsmentioning
confidence: 78%
See 1 more Smart Citation
“…A round-robin among nine different laboratories conducted within the European Metrology Research Programme concluded that the standard deviation of the different calibration values for the same reference cell was 0.81%. 19 An intercomparison of high-efficiency c-Si module calibration between five reference Asian and European laboratories showed a short-circuit current agreement of the same order. 20 Calibration certificates of PV modules measured at STC from accredited laboratories typically declare that uncertainty in short-circuit current, which is closely the same as uncertainty in G when the modules are used as irradiance sensors, is about u CAL G = 1.8%.…”
Section: Uncertainty Derived From G and T C Sensorsmentioning
confidence: 78%
“…Traceability chains for terrestrial c‐Si PV devices' calibration are currently well established. A round‐robin among nine different laboratories conducted within the European Metrology Research Programme concluded that the standard deviation of the different calibration values for the same reference cell was 0.81% 19 . An intercomparison of high‐efficiency c‐Si module calibration between five reference Asian and European laboratories showed a short‐circuit current agreement of the same order 20 .…”
Section: Uncertainty In Pv Module Characterizationmentioning
confidence: 97%
“…We compare these values to measurement uncertainties at ISFH CalTeC, which typically are around ±1.0% (level of confidence of approximately 95% [ 34 ] ) for small and large‐area devices [ 14 ] and to measurement uncertainties from NMI reaching values down to ±0.50%. [ 35 ] For WPVS 1, WPVS 2, and the large‐area reference cell, the relative deviations obtained are smaller than these typical measurement uncertainties. WPVS 3 shows a larger relative deviation of −0.68%, probably caused from the lower wavelength resolution in this region.…”
Section: Discussion and Outlookmentioning
confidence: 92%
“…In addition, as good practice for measurement and testing laboratories, and even required for calibration laboratories accredited to ISO/IEC 17025, 16 in the last 30 years several interlaboratory comparisons and round-robins have already been organised for SJ PV testing at STC. [17][18][19][20][21][22][23][24][25] The World Photovoltaic Scale (WPVS) itself, which nowadays has become a sort of alias to refer to a solar cell with some standardised package, was in fact established in 1999 as measurement scale for PV starting from a dedicated world-wide intercomparison on calibration of PV cells. [26][27][28] Similar measurement comparisons are less numerous and less geographically wide in the case of MJ PV devices.…”
Section: Introductionmentioning
confidence: 99%